INFLUENCE OF CRAWL STROKE FREQUENCY AND AMPLITUDE ON 50-M SWIMMING PERFORMANCE. (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the influence of stroke frequency and amplitude on 50-m swimming performance. The subjects of this study were 11 male swimming athletes aged 15.09 ± 0.71 on average in the national young category. Swimming time and number of strokes were measured by filming and later the average speed (AS), the average stroke amplitude (SA) and the stroke frequency (SF) were calculated. Data of three performance modes were compared: NORMAL - the athletes swam with competition-like amplitude and frequency, FREQUENCY - increased stroke frequency, AMPLITUDE - swimming with the largest amplitude and the lowest stroke frequency possible. The average speeds found for the three modes were 1.70 ± 0.04 m/s, 1.71 ± 0.05 m/s, and 1.60 ± 0.07 m/s, respectively. These results indicate the importance of stroke frequency for Crawl swimming speed comparatively to that of stroke amplitude.
Keywords: swimming; crawl stroke; frequency; amplitude